Aplikácie Mössbauerovej spektrometrie v štúdiu biologických tkanív - Bonková, Ivana; Bujdoš, Marek; Miglierini, Marcel (Chemické listy, 2018)
Mössbauer spectrometry is a progressive method of analysis of materials which is widely used for the study of various molecular and biomolecular systems, as well as various other objects and materials containing Mössbauer nuclides. This work is focused on applications of Mössbauer spectroscopy in the area of studying iron in biological tissues. The results of the published works show that iron in this case is present in the oxidation states Fe II and Fe III , and constitutes a part of molecules, such as ferritin, ferrihydrite, hematite, and haemosiderin. Low-temperature measurements of some types of biological tissues confirmed the presence of paramagnetic and superparamagnetic components.
Keywords: slezina; Iron; výzkum; Humans; tkáně; Brain Chemistry; Chemistry Techniques, Analytical; Mössbauerova spektrometrie; mozek - chemie; Spleen; železo; Tissues; Spectrometry, Fluorescence; Liver; lidé; játra; chemické techniky analytické; Research; fluorescenční spektrometrie